The Determinants of Life Insurance Ownership - Sianipar, Aryanti Sariartha; Hutagalung, Arif Qaedi (University of Merdeka Malang, 2021)
Life insurance ownership has been known as one of alternatives to mitigate the financial risk of a household. Several ethnicities in Indonesia are exposed to financial risk in terms of premature death of family members because there exists cultural traits expenditures. This paper examines the decision to own life insurance among Bataknese in Medan. The determinants of life insurance ownership observed in this study include socioeconomic and demographic factors. Data was analysed using Logit regression of 185 questionnaires after adjustments from 200 responses. The results show that the Batak ethnic in Medan owned personal life insurance because it was driven by the number of credit card limits, age, number of social gathering clan, education, residence ownership status, and bequest motives. Meanwhile, Saur matua life insurance (cultural traits) ownership is driven by factors in the order of the first child in the family, the number of brothers, life expectancy, and the condition of receiving inheritance from parents. Bataknese own life insurance affected by socioeconomic and demographic factors. This research can provide opportunities for the life insurance industry if it wants to add new features of life insurance products that are specific to ethnic groups with similar cultural heritage patterns. DOI: https://doi.org/10.26905/jkdp.v25i1.5112